GRAMMATICAL ERROR ANALYSIS IN EFL SPEAKING PERFORMANCE - Widi Lestari; Setia Muljanto; Lusiana Lestari (Institut Pendidikan Indonesia Garut, 2020)
This study was carried out to analyze the grammatical errror analysis which are made by the students in their speaking performance. It was based on the assumption that grammatical rule has a function in speaking to make the communication clearly and to convey the information in appropriate way. The study was conducted under qualitative methodology by using case study as the appropriate research design. The data source of this research is 1st grade student from the speaking class of English Education major that consisted of 24 students. For collecting the data, the researcher used observation fieldnote and also video record. The writer identified and analyzed data based on the types of error using Dulay’s theory. Based on the finding, the result of this research showed that students made a total errors 318 times divided into four types of errors: omission, addition, misformation, and misordering. From the quantity of each error types, misformation was the highest errors produced by the students. It took 175 times of errors. And omission had 115 times of errors, moreover, 24 errors fell into error of addition, and the last one misordering was the lowest errors produced by the students the total was 5 errors. Actually, errors are necessary in learning a language, especially learning English language as the foreign language. Thus, error analysis also helps the students identify what the errors are made, because the students cannot apply their language acquisition directly without committing error firstly. They cannot achieve the target language perfectly when the errors appear. Error analysis is very advantageous for both learner and teacher. For learner, by paying more attention, the learners are expected to increase their knowledge on the English grammar. Whereas for teachers, hopefully the research can be useful information in teaching process and in the end, the teacher can be able to teach the material appropriately